MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATERI MASALAH SOSIAL MENGGUNAKAN MODEL PEMBELAJARAN COYRSE REVIEW HORAY PADA KELAS IV SD - Kurniawati, Kurniawati Kurniawati; Marliana, Marliana Marliana; Supriati, Nelis (COLLASE (Creative of Learning Students Elementary Education), 2019)
Learning is said to be effective if students get maximum results. Social studies learning outcomes at SDN Sindanglaya 1 are low. This is influenced by the density of the material, boredom, lack of focus and drowsiness. Maximum learning results can be obtained through one of the innovative Course Review Horay learning models. The objectives of this study are: (1) to find out the effectiveness of the Course Review Horay learning model on social studies learning outcomes in social problems of fourth grade students of SDN Sindanglaya 1, Bandung, and (2) to know the application of the Course Review Horay learning model on social studies learning outcomes social class IV students of SDN Sindanglaya 1, Bandung City. This research is a Quasi-Experimental study with the design of Nonequivalent Control Group Design. The research subjects consisted of 52 students with 27 experimental classes and 25 control students. The dependent variable in the study is the result of learning social studies material social problems. The independent variable is the Course Review Horay learning model. Data collection techniques using structured interviews, observation, tests and documentation. Test the research instrument using tests of validity, reliability, power difference and level of difficulty. Prerequisite test for data analysis using the normality test and the similarity of two variances. Learning outcomes data were analyzed by t-test and N-Gain test.